2003
DOI: 10.1002/humu.9186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 21 novel glucokinase (GCK) mutations in UK and European Caucasians with maturity-onset diabetes of the young (MODY)

Abstract: Maturity-onset diabetes of the young (MODY) resulting from mutations in the glucokinase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Among Caucasian tribes, the GCK gene defect is known to be important in the cause of MODY, so called MODY2, and many mutations have been reported from several European ethnic origins [2][3][4][5][6]. In contrast, adult-based sample collection in Japan suggested that mutation in GCK is rare in MODY, and some cases have obese subjects tend to avoid further medical examination until the appearance of nasty subjective symptoms such as excessive urination.…”
Section: Discussionmentioning
confidence: 99%
“…Among Caucasian tribes, the GCK gene defect is known to be important in the cause of MODY, so called MODY2, and many mutations have been reported from several European ethnic origins [2][3][4][5][6]. In contrast, adult-based sample collection in Japan suggested that mutation in GCK is rare in MODY, and some cases have obese subjects tend to avoid further medical examination until the appearance of nasty subjective symptoms such as excessive urination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, taken together with structural modelling and functional characterisation, the results of in silico analyses are consistent with the clinical data, which shows that the GCK T342P substitution is benign and not the cause of diabetes in the individuals reported. Therefore, the variant described in the original family was coincidental and was not causative of their diabetes [4].…”
mentioning
confidence: 95%
“…Surprisingly, of the 29 single nucleotide polymorphisms (SNPs) described within the coding region of the pancreatic isoform, only one (D4N) results in a missense substitution [3]. T342P (c.1024A>C; p.Thr342Pro) has previously been reported as a pathogenic mutation following its identification in a single family (family SQ) [4]. We now report a second, unrelated family (family GB) with this variant and our clinical and functional studies suggest that T342P should be re-classified as a rare, non-pathogenic variant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Women with mutations in GCK [12][13][14][15][16][17] or HNF1A [16,18] often present with GDM. In addition, mutations in IPF1 have been reported in women with GDM [16,19].…”
Section: Introductionmentioning
confidence: 99%